Governance of the Functions Representation and Recruitment of the Golkar Party in Actualize Good Governance in the Reform Era - Agun Gunandjar Sudarsa; Nurliah Nurdin; Muhammad Taufiq; Makhdum Priyatno (Political Science Program, Universitas Negeri Semarang, 2022)
Political parties have a strategic function in actualize of good governance through representation and recruitment functions. The function of representation is a form of accountability of political parties to the public by absorbing aspirations, articulating and aggregating society's interests into laws, regulations, and policies, as well as overseeing the implementation of public policies. The function representation of political parties also includes forming and running an accountable and effective government, controlling corruption, and strengthening political stability. This study aims to analyze the causes of the governance function of representation and recruitment of the Golkar Party as a political party institution that has not optimally actualize good governance in the reform era. This study also formulates a governance model for the representation and recruitment functions of the Golkar Party, which can promote good governance. The research method uses mixed methods or mixed methods research (MMR), combining quantitative and qualitative approaches with exploratory sequential mixed methods models. The theoretical approach used is the political party representation theory of Bartolini Mair (2001), and Szymanek (2015), and the political party recruitment theory approach put forward by Pippa Norris (2006). The results showed that the governance of the function representation of the Golkar Party in the reform era did not function optimally because the function representation was still electoral, and the strong interests and presence of rent-seekers made the Golkar Party not autonomous, not free from oligarchy and corruption. This study recommends an excellent political party governance model with a functional aspirational house model and a model of educational institutions, regeneration, and recruitment.